2020
DOI: 10.1111/cfs.12730
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive foster care: How foster parents support cultural and relational connections for Indigenous children

Abstract: How do foster parents support the relational and cultural connections of Indigenous children in care? The answer matters; the well‐being of Indigenous children depends on these connections. At one of Canada's largest Indigenous child welfare agencies, we implemented inclusive foster care, an approach requiring foster parents to engage with the family, community, and cultural life of the child for whom they care. Fifteen years later, we present findings from a thematic analysis of interviews with 13 foster pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Forty-two articles [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], from 38 unique studies, reported on aspects of Indigenous youth wellbeing in Canada. Our thematic analysis identified eight aspects of wellbeing for this population: basic resources for survival; safety and stability; relationships with others; culture and spirituality; knowledge, opportunities, and the future; identity; resilience and independence; and recreation and interests.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-two articles [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ], from 38 unique studies, reported on aspects of Indigenous youth wellbeing in Canada. Our thematic analysis identified eight aspects of wellbeing for this population: basic resources for survival; safety and stability; relationships with others; culture and spirituality; knowledge, opportunities, and the future; identity; resilience and independence; and recreation and interests.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of having a safe and stable living environment is essential to achieving wellbeing for Indigenous youth in Canada [ 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 52 , 53 , 54 , 55 , 56 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 70 ]. A number of negative incursions undermine the attainment of this safe environment: colonisation and racism [ 40 , 43 , 44 , 45 , 46 , 47 , 49 , 53 , 54 , 55 , 56 , 58 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 81 ] effects include microaggressions, marginalisation, violence, suicide and substance abuse [ 45 , 47 , 49 , 53 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data do offer some indications that well-crafted, well supported structural relationships between foster carers and the child’s Indigenous culture can yield good outcomes. Research published in 2020 [ 69 ] from British Columbia shows what can be accomplished with highly committed partners, willing to stay in intense connection, working on the basis that connection will be continuous and not episodic. This work also indicates that a stronger connection of an Indigenous foster parent to their own culture also acts as a support for better outcomes.…”
Section: Are Children Better Off Growing Up In Care?mentioning
confidence: 99%